Mechanical Performance and Structural Evaluation of Bamboo-Based Hybrid Composites Modified with Carbon Filler and Graphene Oxide - Iskandar Yasin; Nurul Hasan; Widarto Sutrisno; Andi Ibrahim Soumi (Politeknik Siber Cerdika Internasional, 2026)
Background: Bamboo-based composites have attracted attention as sustainable alternatives to conventional structural materials in civil engineering. However, their broader application is often limited by relatively low mechanical performance, weak interfacial bonding between fiber and matrix, and vulnerability to structural failure under loading conditions. Objective: This study aims to evaluate the mechanical performance and structural behavior of bamboo-based hybrid composites modified with carbon filler and graphene oxide (GO) to enhance strength, improve interfacial bonding, and reduce the risk of structural failure. Methods: An experimental and numerical approach was employed. Three composite configurations were fabricated and tested (n = 3 specimens per configuration): unfilled bamboo–epoxy (control), carbon-reinforced, and GO-modified composite. Mechanical properties were evaluated through tensile (ASTM D3039) and Charpy impact tests. Finite element analysis (FEA) using ANSYS Workbench validated experimental findings by comparing stress distribution, strain behavior, and total deformation under a 1000 kN axial tensile load, showing strong agreement (R² up to 0.779). Results: The results show that both carbon filler and GO significantly improve the mechanical properties of bamboo composites. The GO-modified composite exhibited the highest tensile strength and elastic modulus, along with enhanced crack resistance due to improved fiber–matrix adhesion and inhibition of crack propagation. FEA simulations support the experimental findings, demonstrating that GO-modified composites display more uniform stress distribution, lower strain concentration, and reduced deformation compared with the other configurations. Conclusion: GO-reinforced bamboo hybrid composites demonstrate superior mechanical performance and structural stability, indicating strong potential for mitigating structural failure risks.